2009
DOI: 10.1016/j.ijrobp.2009.05.056
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology Modeling of the Radiation Sensitivity Network: A Biomarker Discovery Platform

Abstract: Purpose The discovery of effective biomarkers is a fundamental goal of molecular medicine. Developing a systems-biology understanding of radiosensitivity can enhance our ability of identifying radiation-specific biomarkers. Methods and Materials Radiosensitivity, as represented by the Survival Fraction at 2 Gy (SF2) was modeled in 48 human cancer cell lines. We apply a linear regression algorithm that integrates gene expression with biological variables including: ras status (mut/wt), tissue of origin (TO) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
235
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(239 citation statements)
references
References 43 publications
3
235
0
1
Order By: Relevance
“…88 In a molecular regulatory network model based on mRNA expression profiles, it has been possible to identify 10 hubs of interactions associated to radiosensitivity. 89 It is not clear whether these patterns can be used for all cancers, or they are tissuespecific. Individual NSCLC patients' responses to chemotherapy are highly variable, 90 and similar spread is measured irradiating NSCLC cell lines.…”
Section: Tumour Tissuementioning
confidence: 99%
“…88 In a molecular regulatory network model based on mRNA expression profiles, it has been possible to identify 10 hubs of interactions associated to radiosensitivity. 89 It is not clear whether these patterns can be used for all cancers, or they are tissuespecific. Individual NSCLC patients' responses to chemotherapy are highly variable, 90 and similar spread is measured irradiating NSCLC cell lines.…”
Section: Tumour Tissuementioning
confidence: 99%
“…25 NF-kB is also the most important mediator in radioresistance. 26 Sandur et al concluded that NF-kB dependent cell survival pathway was crucial for radio-resistance in CRC cell lines and that suppression of inducible NF-kB led to radio-sensitivity. 27 We found a decrease in NF-kB p65 expression after single DHA or EPA treatment.…”
Section: Early Apoptosis (%)mentioning
confidence: 99%
“…Nevertheless, some investigations have demonstrated the involvement of several genes, including HDAC1, MDM2, c-Jun, PKC-β, c-Abl and CDK1, in cellular responses to radiation (79)(80)(81). Some of these genes have been studied as potential targets for radiosensitizer development.…”
Section: Targeting Network Flexibilitymentioning
confidence: 99%